Participatory action as a research method with public health nurses. (6th April 2018) - Cusack, Cheryl; Cohen, Benita; Mignone, Javier; Chartier, Mariette J.; Lutfiyya, Zana
Abstract: Aim: This article explores and describes participatory action research (PAR) as a preferred method in addressing nursing practice issues. This is the first study that used PAR with public health nurses (PHNs) in Canada to develop a professional practice model. Background: Participatory action research is a sub‐category of action research that incorporates feminist and critical theory with foundations in the field of social psychology. For nurses, critical analysis of long‐established beliefs and practices through PAR contributes to emancipatory knowledge regarding the impact of traditional hierarchies on their practice. Design: This study used participatory action, a non‐traditional but systematic research method, which assisted participants to develop a solution to a long‐standing organizational issue. Method: The stages of generating concerns, participatory action, acting on concerns, reflection and evaluation were implemented from 2012 ‐ 2013 in an urban Canadian city, to develop a professional practice model for PHNs. Findings: Four sub‐themes specific to PAR are discussed. These are "participatory action research engaged PHNs in development of a professional practice model;" "the participatory action research cycles of "Look, Think, Act" expanded participants' views;" "participatory action research increased awareness of organizational barriers;" and "participatory action research promoted individual empowerment and system transformation." Conclusions: This study resulted in individual and system change that may not have been possible without the use of PAR. The focus was engagement of participants and recognition of their lived experience, which facilitated PHNs' empowerment, leadership and consciousness‐raising.